The Effect of Giving Forest Honey on the Nutritional Status of Stunting Toddlers in Kampar Regency, Riau Province (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
The problem of short children (stunting) is one of the nutritional problems that still the focus of the government until now. One of the reasons is the lack of nutritional consumption in children for 24-59 months will have an impact on their growth and development. Therefore, nutritional intake must contain complete nutrition and all these nutrients can be obtained from honey. Honey can help the body to maintain health and can stimulate appetite, as well as improve nutritional status.The purpose of this study was to determine the effect of giving honey on the nutritional status of stunting toddlers in Kampar district. The number of samples in this study was 25 toddlers The specific target to be achieved is a change in nutritional status and changes in appetite for toddlers by giving honey regularly twice a day as much as 20 grams per day, 10 grams in the morning and 10 grams per day during 30 days. The type of honey given is forest honey from Kampar Regency. The research method used in this study is a quasi-experimental research method with a One group pre-post test design. The research location was conducted in Ranah Singkuang Village, Kampar Regency. This research was conducted in March-April 2021.The results showed that there was an increase in nutritional status based on the indicator of height for age (TB/U), p value = 0.047, although not significant. However, offering honey has not been able to improve the nutritional status of toddlers based on indicators of weight for age (W/U). This is presumably due to many factors, one of which is the consumption of nutrients, especially energy and protein, which is still low, which is below the recommended evaluation. Even the average level of energy consumption is still below 70% of the estimated figure, meaning that it is still below the basal metabolic requirement, so that all energy consumption is used to meet the body's metabolic needs. The low level of energy and protein consumption causes weight gain during the intervention period has not been able to improve the nutritional status of children based on weight for age.